Cultivating Ecologies for Digital Media Work : The Case of English Studies - Braun, Catherine C. (Book collections on Project MUSE., 2014)
The onslaught of the digital age has rapidly redefined the parameters of virtually every aspect of daily life, and the world of academic scholarship is no exception. In English departments across American institutions of higher education, faculty members face an uphill battle in the struggle for professional recognition of their digital works. In Cultivating Ecologies for Digital Media Work, author Catherine C. Braun calls for a shift in thinking about the professional methods and digital goals of the English studies discipline and its central texts. Braun's in-depth study documents English pr.